Diatom valves for the Holocene sediment sequence retrieved from Lake Loitsana, Finland - Shyhrete Shala; Karin Helmens; Stefan Engels; Peter Kuhry; Malin E Kylander; Tomi P Luoto; Sakari Salonen; Minna Väliranta; Jan Weckström (PANGAEA, 2025)
This dataset provides counts of diatom valves for the Holocene sediment sequence retrieved from Lake Loitsana (Finland) in 2008. Counts per taxon are presented against both depth (m) and age (cal ka. BP); total sums for classes of diatoms (e.g. total benthic taxa) and all counts are presented as well. Two age/depths models are presented: the first model represents the original age/depth model applied to the records (Shala et al., 2014; 2017) and the second age/depth model, which is the author-preferred version, presents updated age-estimates derived using the r package extquotesingleBacon extquotesingle (Blaauw and Christensen, 2011). The diatom dataset provides information on Holocene lake ecosystem dynamics and was used to quantitatively reconstruct Total Phosphorous (TP) values of the lake water. A total of 124 samples were selected for diatom analysis. Diatoms were extracted from the sediment following the protocol presented by Battarbee (1986). First, organic matter was oxidized in H2O2 in a water bath (at c. 100 °C). Subsequently, carbonates were removed by 10% HCl treatment (no visible reaction). Clay particles were decanted from 100 ml beakers (2h intervals). Sand grains were removed after five seconds of sedimentation. The residue was mounted in Naphrax® and analysed under a light microscope with X1000 magnification using immersion oil. Flora used for species identification and information on ecological preferences are presented in Helmens et al. (2009). A minimum of 500 diatoms were identified from each sample with the exception of samples at 900-700 cm where diatom abundance was low. All analyses were performed in the laboratories Stockholm University, Sweden.